Nutritional balance and number of leaves as variables for yield prediction of the Horn plantain - Rodríguez, Vianel; Silva, Ana da; Rodríguez, Orlando (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to develop a regression equation for yield estimation of the Horn plantain crop (Musa AAB subgroup platano cv. Horn), with the relationship between the Nutrient Balance Indexes (DRIS-NBI) (X1) and the number of leaves of the plant (X2). Totally at random, 398 foliar samples were collected. The regression equation developed is Y= 30.351** - 8.644** log X1+ 0.27502*X2, with R2 of 0.6206***, with normal distribution of the residuals. By the developed equation, the potential yield of any Horn plantain plantation in the sampling area could be predicted.